The Arctic & Antarctica: Sediment, Limerick City Gallery of Art, Limerick, Ireland, 6th September - 17th November 2019. - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions. Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the Contemporary Sublime. This item contains 1 press release and 19 exhibition views. This item documents 9 of Neudecker's Arctic & Antarctica works exhibited as part of Sediment , a solo survey show at Limerick City Gallery of Art in 2019. An In Conversation between the artist and Arian Koek discussed the works Between Two Tides and On the Other Side as particular ways of trying to calculate and capture the un-measurable and un-describable. Photography: Benjamin Jones. Images used with permission courtesy of the photographer and Limerick City Gallery of Art. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.